Preparation method of activated carbon catalyst for phosgene synthesis

By improving the activated carbon preparation process, vacuum freeze-drying, deep-cold crushing, cold plasma treatment and segmented heating carbonization, activated carbon catalysts with high catalytic activity and heat resistance stability were prepared, solving the problems of short service life and reduced catalytic activity of activated carbon catalysts in the prior art, and achieving efficient and stable catalytic effects in phosgene synthesis.

CN119701915APending Publication Date: 2025-03-28ANHUI DONGZHI GUANGXIN AGROCHEMICAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411707749.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the existing phosgene synthesis reactor, the catalytic activity of the activated carbon catalyst decreases after the use time is extended, resulting in an increase in the free chlorine content in the export phosgene, and the catalyst's heat resistance and stability are insufficient, and its service life is short, resulting in waste of energy and unstable device operation.

Method used

By improving the activated carbon preparation process, the coconut shell powder is treated with vacuum freeze-drying and deep-cold crushing, followed by cold plasma treatment and pre-oxidation treatment, and finally, the mixed nanosiloxane is heated up and the mixed nanosiloxane is grinded to improve the catalytic activity and heat resistance stability of the activated carbon.

Benefits of technology

The prepared activated carbon catalyst has high catalytic activity, heat resistance and stability, long service life, and can effectively reduce the content of free chlorine during phosgene synthesis, improve energy utilization, and improve the stability of the device operation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005154916070000101
    Figure BDA0005154916070000101
Patent Text Reader

Abstract

The invention discloses a preparation method of an activated carbon catalyst for phosgene synthesis, and belongs to the technical field of phosgene synthesis. The invention provides a preparation method of an activated carbon catalyst for phosgene synthesis, which comprises the following steps: by improving an activated carbon preparation process and utilizing the mutual cooperation and synergistic effect of physical and chemical methods, taking coconut shells as a raw material for preparing activated carbon, and performing freeze drying, plasma treatment, soaking and other treatments on the raw material to prepare the activated carbon. And by combining the improvement of pre-oxidation, carbonization and activation processes, the finally prepared active carbon catalyst has the advantages of high activity, high heat-resistant stability and the like, can be suitable for a high-temperature operation environment and is long in service life, and the utilization rate of phosgene synthesis energy is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of phosgene synthesis, and particularly relates to a method for preparing an activated carbon catalyst for phosgene synthesis. Background Art

[0002] Phosgene, also known as carbonyl chloride or phosgene, is an important organic intermediate widely used in dyes, pesticides, medicines, engineering plastics and polyurethane materials. Phosgene has the chemical formula COCl2 and is a colorless gas that is highly toxic and can easily cause suffocation. It is an active electrophilic reagent that is easily hydrolyzed and is a precursor for the production of polyurethane and polycarbonate plastics.

[0003] It is known that carbon monoxide and chlorine are usually used as raw materials in industry, and activated carbon is used as a catalyst to synthesize phosgene. This reaction is highly exothermic. Since this reaction releases a large amount of heat, the reaction heat needs to be removed in time. At present, the phosgene synthesis reactor is mainly a vertical tube-in-tube fixed bed reactor with activated carbon catalyst installed in the tube side and cooling medium in the shell side. If water is used as the cooling medium, high-grade steam cannot be produced, resulting in energy waste and corrosion risks; if high-boiling-point oil is used as the cooling medium, the operating temperature of the reaction tube rises, the activated carbon has poor high temperature resistance and antioxidant properties, the activated carbon is easily ablated and pulverized, the reactor service life is shortened, and the device operation stability is poor.

[0004] As the usage time of activated carbon as a phosgene synthesis catalyst continues to increase, the ability of activated carbon to catalyze phosgene synthesis slowly decreases, resulting in a continuous increase in the free chlorine content in the exported synthetic phosgene.

[0005] In addition, the current improvement methods for phosgene synthesis activated carbon catalysts are mainly to improve their activity and stability through modification, while ignoring the influence of the activated carbon preparation process on the activated carbon function. Therefore, the present application has made great improvements in the current activated carbon preparation and activation process to prepare an activated carbon catalyst with good heat resistance, strong catalytic activity and stability, and long service life. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing an activated carbon catalyst for phosgene synthesis in view of the existing problems.

[0007] The present invention is achieved through the following technical solutions:

[0008] A method for preparing an activated carbon catalyst for phosgene synthesis comprises the following steps:

[0009] S1, after washing the coconut shell, place it in a freeze dryer for vacuum freeze drying, and then perform deep cold crushing to obtain coconut shell powder for standby use;

[0010] S2, placing the coconut shell powder treated by constant temperature immersion of the treatment agent into the reaction chamber of the DBD cold plasma equipment, and turning on the equipment for plasma treatment;

[0011] S3, placing the coconut shell powder after the cold plasma treatment in a tubular heating furnace, and pre-oxidizing it at a constant temperature for 30 to 40 minutes under a constant temperature air condition;

[0012] S4, placing the oxidized coconut shell powder in a muffle furnace, heating it in stages to 600-700°C and carbonizing it for 2-3h at this temperature, then naturally cooling it to room temperature to take out the activated carbon;

[0013] S5. Place nano-siloxane and activated carbon in a bead mill at a weight ratio of 1:90-120 for grinding and mixing. After grinding and mixing, add them to a reactor, then add an activator to the reactor, heat and pressurize for 1-2 hours, and take out and dry after the temperature drops to room temperature.

[0014] Preferably, the vacuum freeze-drying conditions described in step S1 are: pre-freezing temperature -35 to -25°C, pre-freezing time 1 to 2 hours, sublimation temperature -30 to -20°C, sublimation heating time 2 to 4 hours, vacuum degree 20 to 30Pa, drying temperature 20 to 30°C, drying heating time 4 to 8 hours, and vacuum degree 20 to 30Pa.

[0015] Preferably, the conditions of the deep cold pulverization treatment in step S1 are: controlling the temperature in the pulverizer to -60 to -40°C, the rotation speed of the pulverizer to 1000 to 2000 rpm, and the pulverization time to 7 to 15 minutes.

[0016] Preferably, the components and corresponding weight percentages of the treatment agent described in step S2 are: 1.8-2.6% acetic acid, 0.3-0.5% humic acid, 4-8% glycerol, and the balance is water. The constant temperature immersion temperature of the treatment agent is 70-90°C.

[0017] Preferably, the parameters of the plasma treatment in step S2 are: the treatment power is 2 to 5 kW, and the number of treatments is 5 to 11 times.

[0018] Preferably, the constant temperature in step S3 is 200-300°C.

[0019] Preferably, the staged temperature increase treatment in step S4 is firstly increased to 160-180°C at a rate of 2-3°C / min, then increased to 300-350°C at a rate of 5-7°C / min, and finally increased to 600-700°C at a rate of 2-3°C / min.

[0020] Preferably, the grinding speed in step S5 is 2000-3000 rpm, and the grinding time is 8-16 min.

[0021] Preferably, the components and corresponding weight parts of the active agent in step S5 are 2-2.8% methacryloyloxyethyl trimethylammonium chloride, 3-4% tannic acid, 0.9-1.3% sodium citrate, 3-7% sodium dodecylbenzene sulfate, and the balance is water.

[0022] Preferably, the heating and pressurizing in step S5 are specifically: the heating temperature is 160-200° C., and the pressure is 20-30 MPa.

[0023] Compared with the prior art, the present invention has the following advantages:

[0024] The present invention provides a method for preparing an activated carbon catalyst for phosgene synthesis. By improving the activated carbon preparation process and utilizing physical and chemical methods to cooperate with each other, the activated carbon catalyst finally prepared has multiple advantages such as high activity and high heat resistance and stability, can be applied to high-temperature operating environments, and has a long service life, thereby greatly improving the utilization rate of phosgene synthesis energy.

[0025] First, the coconut shell is vacuum freeze-dried and then deep-cold crushed. The whole process is carried out in a low-temperature environment to ensure the stability of the coconut shell performance and dry it thoroughly to avoid residual moisture affecting the carbonization effect. After the treatment agent is soaked, it is treated with cold plasma. Microscopic grooves and pores are formed on the surface of the coconut shell powder, and a large number of oxygen-containing functional groups are generated, which effectively improves the generation rate of activated carbon and the catalytic activity of activated carbon, and lays a good foundation for subsequent pre-oxidation, carbonization and activation. During the heat carbonization process of the coconut shell powder treated with the treatment agent, the moisture and organic matter in the treatment agent and the pores are Overflow has an acid hydrolysis effect on the cellulose structure of coconut shell, resulting in obvious holes, and then pre-oxidation treatment is carried out. The pre-oxidation process helps the Cls peak of activated carbon to move in the direction of higher binding energy, further increase the number of oxygen-containing functional groups, form more chemical bonds between oxygen and carbon groups, and improve the heat resistance of activated carbon. In addition, the pretreatment and pre-oxidation of raw materials inhibit the formation of oxygen bridges between C1 and C6 and then generate L-glucose. By preventing the production of L-glucose, the formation of tar is inhibited, avoiding tar blocking the pores in the subsequent carbonization process, increasing the porosity, and further improving the catalytic effect.

[0026] Secondly, the carbonization treatment is carried out in a staged heating method. By adjusting the heating rate, the carbonization efficiency is improved, the formation of micropores is promoted, and the reaction activity is further improved, the reaction selectivity is increased, and the diffusion and forward movement of the reaction products are increased, thereby reducing the accumulation of the catalyst. The microporous structure is more stable and the service life of the activated carbon is longer.

[0027] Finally, activation treatment is carried out. The grinding treatment and activator treatment have a synergistic effect. After the nano-siloxane and activated carbon are ground and mixed, the activator treatment is carried out. The nano-siloxane is adsorbed into the pores of the activated carbon or adsorbed on the surface of the activated carbon, which not only increases the surface area of ​​the activated carbon but also improves the heat resistance and stability of the activated carbon. DETAILED DESCRIPTION

[0028] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] A method for preparing an activated carbon catalyst for phosgene synthesis comprises the following steps:

[0031] S1, after washing the coconut shell, place it in a freeze dryer for vacuum freeze drying, specifically pre-freezing temperature -35 ° C, pre-freezing time 1h, sublimation temperature -30 ° C, sublimation heating time 2h, vacuum degree 20Pa, drying temperature 20 ° C, drying heating time 4h, vacuum degree 20Pa, and then perform deep cold crushing, control the temperature in the crusher to -60 ° C, the speed of the crusher is 1000rpm, crush 7min to obtain coconut shell powder for standby;

[0032] S2, putting the coconut shell powder soaked in the treatment agent at 70°C into the reaction chamber of the DBD cold plasma equipment, turning on the equipment for plasma treatment, the treatment power is 2kW, and the number of treatments is 5 times;

[0033] The components and corresponding weight percentages in the treatment agent are: 1.8% acetic acid, 0.3% humic acid, 4% glycerol, and the balance is water;

[0034] S3, placing the coconut shell powder after the cold plasma treatment in a tubular heating furnace, and pre-oxidizing it at a constant temperature of 200° C. for 30 minutes;

[0035] S4, placing the oxidized coconut shell powder in a muffle furnace, first raising the temperature to 160°C at a rate of 2°C / min, then raising the temperature to 300°C at a rate of 5°C / min, and finally raising the temperature to 600°C at a rate of 2°C / min and carbonizing at this temperature for 2h, then naturally cooling to room temperature and taking out the activated carbon;

[0036] S5, placing nano-siloxane and activated carbon in a bead mill at a weight ratio of 1:90 at 2000 rpm for 8 min, adding the ground and mixed mixture into a reactor, then adding an activator into the reactor, heating and pressurizing at 160° C. and 20 MPa for 1 h, and taking out and drying after the temperature drops to room temperature;

[0037] The components and corresponding weight parts in the active agent are 2% of methacryloyloxyethyl trimethyl ammonium chloride, 3% of tannic acid, 0.9% of sodium citrate, 3% of sodium dodecylbenzene sulfate, and the balance is water.

[0038] Example 2

[0039] A method for preparing an activated carbon catalyst for phosgene synthesis comprises the following steps:

[0040] S1, after washing the coconut shell, place it in a freeze dryer for vacuum freeze drying, specifically pre-freezing temperature -30 ° C, pre-freezing time 1.5h, sublimation temperature -25 ° C, sublimation heating time 3h, vacuum degree 25Pa, drying temperature 25 ° C, drying heating time 6h, vacuum degree 25Pa, and then perform deep cold crushing, control the temperature in the pulverizer to -50 ° C, the rotating speed of the pulverizer is 1500rpm, and the coconut shell powder is obtained after crushing for 11min for standby use;

[0041] S2, putting the coconut shell powder soaked in the treatment agent at 80°C into the reaction chamber of the DBD cold plasma equipment, turning on the equipment for plasma treatment, the treatment power is 3.5kW, and the number of treatments is 8 times;

[0042] The components and corresponding weight percentages in the treatment agent are: acetic acid 2.2%, humic acid 0.4%, glycerol 6%, and the balance is water;

[0043] S3, placing the coconut shell powder after the cold plasma treatment in a tubular heating furnace, and pre-oxidizing it at a constant temperature of 250° C. for 35 minutes;

[0044] S4, placing the oxidized coconut shell powder in a muffle furnace, firstly raising the temperature to 170°C at a rate of 2.5°C / min, then raising the temperature to 325°C at a rate of 6°C / min, and finally raising the temperature to 650°C at a rate of 2.5°C / min and carbonizing at this temperature for 2.5h, then naturally cooling to room temperature and taking out the activated carbon;

[0045] S5, grinding the nano-siloxane and activated carbon in a bead mill at 2500 rpm for 12 min in a weight ratio of 1:105, adding the grinding mixture to a reactor, and then adding the activator to the reactor, heating and pressurizing at 180°C and 25MPa for 1.5h, and taking out and drying after the temperature drops to room temperature;

[0046] The components and corresponding weight parts in the active agent are 2.4% of methacryloyloxyethyl trimethyl ammonium chloride, 3.5% of tannic acid, 1.1% of sodium citrate, 5% of sodium dodecylbenzene sulfate, and the balance is water.

[0047] Example 3

[0048] A method for preparing an activated carbon catalyst for phosgene synthesis comprises the following steps:

[0049] S1, after washing the coconut shell, place it in a freeze dryer for vacuum freeze drying, specifically pre-freezing temperature -25 ° C, pre-freezing time 2h, sublimation temperature -20 ° C, sublimation heating time 4h, vacuum degree 30Pa, drying temperature 30 ° C, drying heating time 8h, vacuum degree 30Pa, and then perform deep cold crushing, control the temperature in the crusher to -40 ° C, the speed of the crusher is 2000rpm, crushing 15min to obtain coconut shell powder for standby;

[0050] S2, putting the coconut shell powder soaked in the treatment agent at 90°C into the reaction chamber of the DBD cold plasma equipment, turning on the equipment for plasma treatment, the treatment power is 5kW, and the number of treatments is 11 times;

[0051] The components and corresponding weight percentages in the treatment agent are: acetic acid 2.6%, humic acid 0.5%, glycerol 8%, and the balance is water;

[0052] S3, placing the coconut shell powder after the cold plasma treatment in a tubular heating furnace, and pre-oxidizing it at a constant temperature of 300° C. in air for 40 minutes;

[0053] S4, placing the oxidized coconut shell powder in a muffle furnace, first raising the temperature to 180°C at a rate of 3°C / min, then raising the temperature to 350°C at a rate of 7°C / min, and finally raising the temperature to 700°C at a rate of 3°C / min and carbonizing at this temperature for 3 hours, then naturally cooling to room temperature and taking out the activated carbon;

[0054] S5, grinding the nano-siloxane and activated carbon in a bead mill at 3000 rpm for 16 min in a weight ratio of 1:120, adding the grinding mixture to a reactor, and then adding the activator to the reactor, heating and pressurizing at 200°C and 30MPa for 2h, and taking out and drying after the temperature drops to room temperature;

[0055] The components and corresponding weight parts in the active agent are 2.8% of methacryloyloxyethyl trimethyl ammonium chloride, 4% of tannic acid, 1.3% of sodium citrate, 7% of sodium dodecylbenzene sulfate, and the balance is water.

[0056] Comparative Example 1

[0057] On the basis of Example 2, no treatment agent immersion treatment is performed in S2, and the rest of the technical scheme is consistent with the technical scheme of Example 2.

[0058] Comparative Example 2

[0059] On the basis of Example 2, plasma treatment is not performed in S2, and the rest of the technical solutions are consistent with those of Example 2.

[0060] Comparative Example 3

[0061] On the basis of Example 2, the entire processing step of S2 is not performed, and the rest of the technical scheme remains consistent with the technical scheme of Example 2.

[0062] Comparative Example 4

[0063] On the basis of Example 2, the entire step of S3 is not performed, and the rest of the technical solutions remain consistent with the technical solutions of Example 2.

[0064] Comparative Example 5

[0065] On the basis of Example 2, no staged temperature increase treatment is performed in S4, and the temperature is directly increased to 650°C at 2.5°C / min. The rest of the technical scheme is consistent with the technical scheme of Example 2.

[0066] Comparative Example 6

[0067] On the basis of Example 2, in S5, the nano-siloxane and activated carbon are directly mixed in a ratio of 1:105 and added into the reactor without grinding treatment, and the rest of the technical scheme is consistent with the technical scheme of Example 2.

[0068] Comparative Example 7

[0069] On the basis of Example 2, the entire processing step of S5 is not performed, and the rest of the technical solutions are consistent with the technical solutions of Example 2.

[0070] 1. Characterization of active catalysts

[0071] The specific surface area and pore structure of the activated carbon catalyst samples of the above-mentioned embodiments and comparative examples were analyzed using a NOVA-2000 fully automatic physical and chemical adsorption instrument produced by Quantachrome Corporation of the United States.

[0072] The results are shown in Table 1 below.

[0073] Table 1 Pore structure parameters of activated carbon catalysts in various embodiments and comparative examples

[0074]

[0075]

[0076] From the comparison of the test data in Table 1, it can be found that the pore structure of the activated carbon catalyst prepared by the method of the present invention has significant advantages, that is, the present invention has good catalytic activity and stability.

[0077] From the test data of Example 2 and Comparative Examples 1 to 3, it can be found that Example 2 has obvious advantages over Comparative Examples 1 to 3 in terms of specific surface area, pore volume, average pore diameter and microporosity of the catalyst, and the effects of Comparative Examples 1 and 2 are significantly better than those of Comparative Example 3, indicating that the treatment agent immersion and plasma treatment work synergistically to increase the specific surface area, pore volume, pore diameter, etc. of the activated carbon, which means a better catalytic effect.

[0078] From the test data of Example 2 and Comparative Examples 4 and 5, it can be found that the specific surface area, micropore specific surface area, pore volume, etc. of Example 2 are more significant than those of Comparative Examples 4 and 5, indicating that pre-oxidation can promote micropore growth, which is beneficial to the subsequent carbonization and activation process, and thus helps to further increase the total specific surface area and micropore specific surface area, and pre-oxidation inhibits the generation of oxygen bridges between C1 and C6 and then generates L-glucose, inhibits the generation of tar by preventing the generation of L-glucose, avoids tar blocking pores in the subsequent carbonization process, increases porosity, and further enhances the catalytic effect. And the microporosity of Comparative Example 5 is only 73.86%, indicating that staged heating is conducive to the formation of micropores, thereby improving the activity and stability of the catalyst and extending the service life of the catalyst.

[0079] From the test data of Example 2 and Comparative Examples 6 and 7, it can be found that compared with Comparative Examples 6 and 7, the specific surface area, micropore specific surface area, pore volume, etc. of Example 2 are more significant, and the grinding treatment and the activator treatment have a synergistic effect. After the nano-siloxane and activated carbon are ground and mixed, the activator treatment is carried out, and the nano-siloxane is adsorbed into the pores of the activated carbon or adsorbed and attached to the surface of the activated carbon, which not only increases the surface area of ​​the activated carbon but also improves the heat resistance stability of the activated carbon.

[0080] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field within the technical scope disclosed by the present invention and the technical solution and inventive concept thereof, which are equivalently replaced or changed, should be covered by the protection scope of the present invention.

Claims

1. A method for preparing an activated carbon catalyst for phosgene synthesis, characterized in that: The steps include: S1, after washing the coconut shell, place it in a freeze dryer for vacuum freeze drying, and then perform deep cold crushing to obtain coconut shell powder for standby use; S2, placing the coconut shell powder treated by constant temperature immersion of the treatment agent into the reaction chamber of the DBD cold plasma equipment, and turning on the equipment for plasma treatment; S3, placing the coconut shell powder after the cold plasma treatment in a tubular heating furnace, and pre-oxidizing it at a constant temperature for 30 to 40 minutes under a constant temperature air condition; S4, placing the oxidized coconut shell powder in a muffle furnace, heating it in stages to 600-700°C and carbonizing it for 2-3h at this temperature, then naturally cooling it to room temperature to take out the activated carbon; S5. Place nano-siloxane and activated carbon in a bead mill at a weight ratio of 1:90-120 for grinding and mixing. After grinding and mixing, add them to a reactor, then add an activator to the reactor, heat and pressurize for 1-2 hours, and take out and dry after the temperature drops to room temperature.

2. The method for preparing an activated carbon catalyst for phosgene synthesis according to claim 1, characterized in that: The vacuum freeze-drying conditions described in step S1 are: pre-freezing temperature -35 to -25°C, pre-freezing time 1 to 2 hours, sublimation temperature -30 to -20°C, sublimation heating time 2 to 4 hours, vacuum degree 20 to 30 Pa, drying temperature 20 to 30°C, drying heating time 4 to 8 hours, and vacuum degree 20 to 30 Pa.

3. The method for preparing an activated carbon catalyst for phosgene synthesis according to claim 1, characterized in that: The conditions of the deep cold pulverization treatment in step S1 are: controlling the temperature in the pulverizer to -60 to -40°C, the rotation speed of the pulverizer to 1000 to 2000 rpm, and the pulverization time to 7 to 15 minutes.

4. The method for preparing an activated carbon catalyst for phosgene synthesis according to claim 1, characterized in that: The components and corresponding weight percentages of the treatment agent in step S2 are: 1.8-2.6% acetic acid, 0.3-0.5% humic acid, 4-8% glycerol, and the balance is water. The constant temperature immersion temperature of the treatment agent is 70-90°C.

5. The method for preparing an activated carbon catalyst for phosgene synthesis according to claim 1, characterized in that: The parameters of the plasma treatment in step S2 are: the treatment power is 2-5 kW, and the number of treatments is 5-11 times.

6. The method for preparing an activated carbon catalyst for phosgene synthesis according to claim 1, characterized in that: The constant temperature in step S3 is 200-300°C.

7. The method for preparing an activated carbon catalyst for phosgene synthesis according to claim 1, characterized in that: The stepwise temperature increase treatment in step S4 is specifically to first increase the temperature to 160-180°C at a rate of 2-3°C / min, then increase the temperature to 300-350°C at a rate of 5-7°C / min, and finally increase the temperature to 600-700°C at a rate of 2-3°C / min.

8. The method for preparing an activated carbon catalyst for phosgene synthesis according to claim 1, characterized in that: The grinding speed in step S5 is 2000-3000 rpm, and the grinding time is 8-16 min.

9. The method for preparing an activated carbon catalyst for phosgene synthesis according to claim 1, characterized in that: The components and corresponding weight parts of the active agent in step S5 are 2-2.8% methacryloyloxyethyl trimethyl ammonium chloride, 3-4% tannic acid, 0.9-1.3% sodium citrate, 3-7% sodium dodecylbenzene sulfate, and the balance is water.

10. The method for preparing an activated carbon catalyst for phosgene synthesis according to claim 1, characterized in that: The heating and pressurizing in step S5 are specifically: the heating temperature is 160-200° C., and the pressure is 20-30 MPa.